Research cooperation between universities and businesses as a source of innovativeness - Firlej, Krzysztof Adam (Współpraca badawcza uniwersytetów i przedsiębiorstw jako źródło innowacyjności, 2020)
The aim of this article is to determine the extent to which research cooperation between universities and businesses affects the results of innovative activities. A research hypothesis has been adopted that there is a very high level of interdependence between the research cooperation of universities and businesses and the effects in the area of economic innovation. In order to empirically verify the proposed research hypothesis, the correlation relationship between the variable of university-business research cooperation in 2013-2017 and selected variables determining the effects of innovation activity in 2018 in EU economies was examined. The results obtained in the study allowed for a positive verification of the research hypothesis, confirming the important role of research cooperation between universities and businesses in the context of creating innovation in the economy
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 6, s. 65-75